(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of the study to estimate the prevalence of malaria amongst the population with fever or history of fever at sukkur. Study Design: Cross sectional study Place and Duration of Study: This study conducted at laboratory Ghulam Mohammad Mahar Medical College Hospital Sukkur from January 2011 to December 2012. Materials and Methods: Total 1746 clinical suspected case of malaria were included in the study. Patients presenting with fever were screened, thick and thin blood films prepared on microscopic glass slide, stained with 5% Giemsa’s stain. Results: There were 344 cases below 11 years, 590 cases between 11 to 20 years.812 cases above 20 years. They were 960 males and 786 females, with male to female ratio 1.2:1 .The prevalence of plasmodium slide positivity was 7.9% (138/1746). Among plasmodium slide positive, 60.5% (83/138) were positive for P.vivax and 39.5% (55/138) were positive for P. falciparum. Conclusion: Identification of malaria cases in early acute phase of disease is significant for proper curative treatment. Anti mosquito eradication measures should be taken for breeding places of vector with personal protection measures and awareness program for malaria should be initiated.